Sinergi Kecerdasan Intelektual dan Articial Intelligence dalam Pengembangan SDM Guru Melalui Fungsi Manajemen di SMK Al Imron Sumenep - Abidin, Zeinal; Maizah, St.; Saputra, Mohammad Irsyad Wira (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
The era of Industry 4.0 and Society 5.0 demands adaptive readiness among vocational educators to integrate artificial intelligence (AI) into teaching practices. This article analyzes human resource development strategies for teachers at SMK Al Imron Sumenep through the POAC management framework (Planning, Organizing, Actuating, Controlling) to foster optimal synergy between teachers' intellectual capabilities and AI. Employing a descriptive qualitative approach based on field studies and managerial analysis, the findings reveal that systematic implementation of POAC accelerates school digital transformation, enhances administrative efficiency, improves instructional module development, and strengthens graduate workforce readiness. The controlling phase, supported by digital audits, ensures ethical, measurable, and quality-oriented AI utilization. In conclusion, the POAC framework successfully positions AI as an intellectual partner that optimizes teachers' pedagogical and administrative competencies without diminishing their humanistic role. Sustaining this strategy requires visionary instructional leadership, continuous professional development, and institutional policy support. These findings offer a practical model for vocational schools in managing sustainable human-technology synergy.